2017
DOI: 10.1200/jco.2017.72.2348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Early [18F]Sodium Fluoride Positron Emission Tomography/Computed Tomography Response to Treatment in Men With Metastatic Prostate Cancer to Bone

Abstract: Purpose [F]Sodium fluoride (NaF) positron emission tomography (PET)/computed tomography (CT) is a promising radiotracer for quantitative assessment of bone metastases. This study assesses changes in early NaF PET/CT response measures in metastatic prostate cancer for correlation to clinical outcomes. Patients and Methods Fifty-six patients with metastatic castration-resistant prostate cancer (mCRPC) with osseous metastases had NaF PET/CT scans performed at baseline and after three cycles of chemotherapy (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 23 publications
2
64
1
Order By: Relevance
“…tumors that are spatially and temporally separated. No such imaging modalities are currently employed in standard clinical practice, which are usually instead employed to determine tumor size and/or localization (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…tumors that are spatially and temporally separated. No such imaging modalities are currently employed in standard clinical practice, which are usually instead employed to determine tumor size and/or localization (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of F18-labeled fluordeoxyglucose allows more direct visualization of the tumor, but interpretation may be confounded by the presence of osteoblastic remodeling within the responding tumor microenvironment. 16 Additional tumor-specific positron emission tomography probes, such as prostate-specific membrane antigen, choline, fluciclovine, or dihydrotestosterone, 17,18 may provide useful discrimination in this clinical setting, where bone imaging results are disconnected from PSA, soft-tissue imaging, and patient symptoms, provided that proper analytic and clinical validation studies are performed in this mCRPC setting. Our work highlights this unmet need for functional bone imaging over time to more fully assess patient benefits.…”
Section: Research Original Investigationmentioning
confidence: 99%
“…The measurement of total skeletal metastatic burden is possible with 18F‐fluoride PET as there is generally high contrast between metastases and normal bone. In prostate cancer, a number of studies have shown that global quantitative metrics can predict treatment response and progression‐free survival or overall survival …”
Section: Pet and Pet/ctmentioning
confidence: 99%